Azure Arc - up and running : explore the new-generation hybrid cloud and learn how to build Azure Arc-enabled solutions /: explore the new-generation hybrid cloud and learn how to build Azure Arc-enabled solutions. (2021) - Malik, Amit; Kaur, Daman
No abstract available